Politeness Strategies Between English Department Students at Dharma Andalas University - Anissa Tulfadilla; Widya Fhitri; Yalmiadi Yalmiadi; Rahma Yanti (Fakultas Sastra Universitas Ekasakti, 2023)
The strategy of politeness, and sentence structures are all described and explained in this research of Dharma Andalas University English Department students. Descriptive qualitative analysis is used in this study. A discourse between students studying English literature serves as the research's data source. Data retrieval through the refer technique. This is followed by an open-ended, participatory manner. Data were gathered by recording discussions between Andalas Dharma University English literature students. The study's findings indicate that students of English literature frequently employ sentences that are followed by a request sentence in their interactions with other students of the same subject.The study's findings indicate that students of English Department frequently employ sentences that are followed by a request sentence in their interactions with other students of the same subject. Positive politeness is the most commonly utilized kind. This suggests that the English literature students communicate with a high degree of civility. Positive politeness is most commonly utilized. This suggests that English literature students communicate with excellent manners.